HYDROPOWER DAM AND HYDROLOGICAL ALTERATION ON THE DA RIVER IN SON LA, VIETNAM - Thi Yen, Chao; Picco, Lorenzo; Xuan Dung, Bui; Quang Bao, Tran (Journal of Forestry Science and Technology, 2019)
The Da River basin, the largest tributary of the Red River, has experienced a rapid development of hydropower dams, of which Son La hydropower plant is the biggest and the most complex dam project ever built in Vietnam. The study was aimed to examine the hydrological alterations after the construction of Son La hydropower dam in downstream of the Da in pre- and post-dam period. The flow regime information from 1961 to 2016 was obtained from the Vietnam Meteorological and Hydrological Administration. The hydrological alteration was quantified by using IHA (Indicators of Hydrologic Alteration). The Kruskal – Wallis test was applied to examine the changes of hydrological regime between pre- and post- dam period. The results showed that 4 groups of IHA had significant change and one group had no significant difference in pre- and post-dam period. Particularly, the flow in rainy season decreased between 5% and 43% and increased average 71.6% in dry season in the post-impact period. Minima and maxima of 1-, 3-, 7-, 30-, and 90-days flow had a broad fluctuation with a reduction of mean flow between 37% and 90%, except 30- and 90-day minimum having an upward trend of 6% and 129%, in the order. The low and high pulse count increased 40% and 100% in post-2010, respectively, whereas the low pulse duration decreased 60% in the post-dam period. Fall rate had greater fluctuation than rise rate with an increase of 123% compared to the change of +57%, in the order.